Pengaruh Lingkungan Kerja, Motivasi Kerja, Disiplin Kerja, Dan Komunikasi Kerja Terhadap Kinerja Pegawai Pada Kantor Pertanahan Kota Probolinggo - Atmaja, Muhammad Luhung Yudha; Ngatimun, Ngatimun; Dhany, Umy Rahma (Universitas Panca Marga, 2024)
The study aims to determine the effect of work environment, work motivation, work discipline, and work communication partially and the most dominant influence on employee performance at the Probolinggo City Land Office. The type of research used is a causal associative approach, with variables consisting of independent variables, namely work environment, work motivation, work discipline, and work communication and the dependent variable is employee performance. The population in this study amounted to 60 and the sample used amounted to 60 employees of the Probolinggo City Land Office based on certain criteria, namely employees of the State Civil Apparatus (ASN) and Non-Government Employees (PNP). The data sources used in this study come from primary data and secondary data, with the help of the PLS 3 application. The results of the study determined that the work environment variable (X1) had a significant and positive effect on employee performance (Y). Work motivation variable (X2) has a significant and positive effect on employee performance (Y). Work discipline variable (X3) has a significant and positive effect on employee performance (Y). Work communication variable (X4) has a significant and positive effect on employee performance (Y). The most dominant variable test shows that the work environment variable (X1) has the most dominant influence on employee performance (Y). Because the work environment has a stronger influence on employee performance, it is the first priority in improving the performance of Probolinggo City Land Office employees.